The Hegel-Marx Connection - Burns, T. author. aut Link
VIII, 258 p.
Keywords: A major and timely re-examination of key areas in the social and political thought of Hegel and Marx. The editors' extensive introduction surveys the development of the connection from the Young Hegelians through the main Marxist thinkers to contemporary debates. Leading scholars including Terrell Carver, Chris Arthur and Gary Browning debate themes such as: the nature of the connection itself; scientific method; political economy; the Hegelian basis to Marx's 'Doctoral Dissertation'; human needs; history and international relations.